Menilik Nazar Dalam Kajian Dogmatis Serta Relevansinya Bagi Jemaat Huria Kristen Indonesia - Puspita Sari Panjaitan, Angria; Munthe, Pardomuan (P3M STT Kristus Alfa Omega, 2025)
The practice of making vows has been found to potentially deviate from its authentic theological meaning among members of the Huria Kristen Indonesia (HKI) Special Resort Tarutung. Preliminary observations indicate that some congregants tend to understand vows in a transactional manner, perceiving them as a form of